Silicone-based antibacterial agent and method for preparing the same
Patent Information
- Application Number
- CN202611091639.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-16
AI Technical Summary
然而,这类长链季铵三烷氧基硅烷官能度高,水解缩合速率极快,在水相中极易由于过度缩聚而导致产品在储存过程中出现不可逆的凝胶化
在本发明中,单体A含三烷氧基和长链季铵基团,缩合反应官能度高;单体B含两个烷氧基,缩合后主要形成D型二官能硅氧烷骨架。第一阶段富集单体A并仅加入部分单体B,二者先发生共水解和低聚反应,以此降低体系内游离单体A含量,避免后续引入阴离子乳液时大量游离单体A直接暴露。单体B的加入量限制在总量的20-45%,以避免第一阶段过早形成过长的疏水骨架或造成相分离。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of antibacterial liquid silicone rubber composition preparation technology, specifically relating to an organosilicon-based antibacterial agent and its preparation method. Background Technology
[0002] To impart long-term antibacterial properties to liquid silicone rubber, it is usually necessary to introduce functional groups with bactericidal activity into the siloxane structure. Among them, quaternary ammonium salt groups are widely used in the preparation of organosilicon antibacterial materials due to their broad-spectrum antibacterial properties, high stability, and non-migration characteristics. Quaternary ammonium salt antibacterial agents typically rely on the electrostatic interaction between the positively charged quaternary ammonium groups and the surface of microbial cells, and the disturbance of the cell membrane by long-chain hydrophobic groups, leading to the loss of intracellular substances and thus killing microorganisms. However, although low-molecular-weight quaternary ammonium salts have a relatively fast antibacterial effect, they are extremely easy to dissolve and migrate, resulting in an antibacterial effect that often depends on the continuous release of active substances. This not only lacks persistence in antibacterial efficacy but also poses a risk to the environment and ecology. To improve the adhesion of quaternary ammonium salts to the substrate surface, existing technologies often use long-chain quaternary ammonium alkoxysilanes. These monomers contain hydrolyzable silanoxy groups, which hydrolyze in an aqueous medium to form active silanols, and further condense with themselves or hydroxyl-containing substrates through dehydration condensation reactions, thereby covalently fixing the quaternary ammonium groups to the surface. However, these long-chain quaternary ammonium trialkoxysilanes have high functionality and extremely fast hydrolysis-condensation rates. In aqueous phases, they are prone to excessive polymerization, leading to irreversible gelation during storage. Simultaneously, quaternary ammonium salts carry a high density of positive charges. When introduced as antibacterial additives into anionicly stable emulsions, they readily undergo strong charge neutralization and complexation reactions with anionic emulsifiers, dispersants, or negatively charged latex particles, causing emulsion flocculation, sudden increases in viscosity, filtration residue, or coating defects.
[0003] Therefore, designing a modified polysiloxane that can exist stably in the aqueous phase, exhibits excellent compatibility with anionic emulsions, and also has efficient antibacterial properties is a problem that urgently needs to be solved in the field of polymeric organosilicon materials. Summary of the Invention
[0004] To address at least one of the aforementioned problems, this invention provides an organosilicon-based antibacterial agent and its preparation method. The antibacterial agent is prepared from raw materials comprising monomers A, B, C, D, and E, wherein: monomer A is a long-chain alkyl quaternary ammonium trialkoxysilane, monomer B is a dialkyl diekoxysilane, monomer C is a polyether trialkoxysilane, monomer D is a trialkyl monoalkoxysilane, and monomer E is an epoxy-functionalized trialkoxysilane. The preparation method includes the following steps: S1. Solution preparation and acidification: Mix deionized water, nonionic surfactant and polyol, and adjust the pH of the system to 3.7-4.2 with organic acid; S2, First-stage hydrolysis and oligomerization: Add 70-100% of the total amount of monomer A and 20-45% of the total amount of monomer B at 25-32℃. The amount of monomer C added in the first stage shall not exceed 20% of the total amount of monomer C, and the amount of monomer D added in the first stage shall not exceed 40% of the total amount of monomer D. After the addition is completed, hydrolyze for 60-120 minutes and keep warm at 42-47℃ for 30-60 minutes to obtain the first-stage oligomer. S3, Second stage co-condensation: Add the remaining amount of monomer C, monomer D, monomer A, monomer B and monomer E within 90-150 min at 45-50℃. S4. Thermal polycondensation: Polycondensate at 50-56℃ for 1.5-3.5h to obtain a coarse dispersion of polycondensate; S5. Staged de-alcoholization and post-treatment: Vacuum is established stepwise at 48-53℃ to remove hydrolysis by-product alcohols and low-boiling alcohols carried by the raw materials. After cooling, the pH is adjusted and water is added to make up the volume to obtain the product antibacterial agent.
[0005] Furthermore, the specific preparation method includes the following steps: S1. Add initial deionized water, polyol and nonionic surfactant to the reactor, and stir for 10-20 minutes at 25±2℃ and 400-700r / min to form a uniform bottom liquid. Then adjust the pH of the system to 3.7-4.2 with 10wt% acetic acid. S2. Start high shear. At 25-32℃, add first-stage monomer A within 20-60 min, and add first-stage monomer B and first-stage deionized water together within 20-60 min. After the addition is completed, reduce the rotation speed and introduce inert gas to make the system under slight positive pressure. Hydrolyze at 25-32℃ for 60-120 min, then raise the temperature to 42-47℃ and hold for 30-60 min to obtain the first-stage oligomer. S3. Prepare a premix of monomers B, C and E for the second stage in a dry, closed reactor; add the premix and deionized water for the second stage together at 45-50℃ and high shear for 90-150 min, and add monomer D 35-55 min after the addition, maintaining the pH of the system at 3.7-4.2 during the addition process. S4. After feeding, reduce the rotation speed and polycondense at 50-56℃ for 1.5-3.5 hours, taking samples for testing at fixed intervals; S5. Vacuum is applied in stages at 40-53℃ and 350-500r / min. The fractions are collected in stages for testing. Once the standard is reached, the process is stopped, the vacuum is released, and the product antibacterial agent is obtained by adjusting the volume, pH, and filtration.
[0006] Furthermore, the general structural formula of monomer A is: [R 1 N +(CH3)2(CH2)3Si(OR 2 )3]X - , where R 1 It is a C12-C18 straight-chain or branched alkyl group, preferably octadecyl, R 2 Methyl or ethyl, X - The monomers are chloride or bromide ions; monomer B is dimethyldimethoxysilane or dimethyldiethoxysilane, preferably dimethyldiethoxysilane; monomer C is polyethertrimethoxysilane or polyethertriethoxysilane; monomer D is trimethylmethoxysilane or trimethylethoxysilane, preferably trimethylmethoxysilane; monomer E is 3-glycidoxypropyltrimethoxysilane or 3-glycidoxypropyltriethoxysilane, preferably 3-glycidoxypropyltrimethoxysilane.
[0007] Furthermore, during the preparation process, the molar ratio of monomer A: monomer B: monomer C: monomer D: monomer E is (15-30):(45-65):(10-20):(5-12):(1-5); preferably, the molar ratio of monomer A: monomer B: monomer C: monomer D: monomer E is (18-25):(50-58):(12-17):(7-10):(1-4).
[0008] Furthermore, in the first stage, 90-100% of the total amount of monomer A and 25-40% of the total amount of monomer B are added, and monomers C and D are not added in the first stage; in the second stage, all monomers C, all monomers D, the balance of monomer A, the balance of monomer B, and monomer E are added.
[0009] Furthermore, the nonionic surfactant is an EO / PO block polyether and / or an alkyl glycoside; the polyol is propylene glycol and / or dipropylene glycol.
[0010] Furthermore, the organic acid is one or more of acetic acid, lactic acid, and citric acid.
[0011] Further, in step S5, the stepwise vacuum establishment is as follows: the absolute pressure is successively reduced from 50-70 kPa to 35-50 kPa, and then reduced to 20-35 kPa; and the residual methanol content in the product is controlled to be no higher than 0.10 wt% and the residual ethanol content is no higher than 0.50 wt%, with gas chromatography detection as the endpoint.
[0012] An organosilicon-based antibacterial agent is prepared by the preparation method of an organosilicon-based antibacterial agent as described in any of the above technical solutions; the antibacterial agent has a non-volatile content of 20-30 wt%, a pH of 4.7-5.2, and no visible lumps after filtration through a 100 μm sieve.
[0013] An anionic stabilized aqueous composition comprising a polymer emulsion and an antibacterial agent as described in any of the above technical solutions, wherein the antibacterial agent (calculated as non-volatile matter of the antibacterial agent) accounts for 0.05-1.5 wt% of the total mass of the aqueous composition.
[0014] Furthermore, the polymer emulsion is one or more of the following: styrene-acrylate emulsion, pure acrylate emulsion, vinyl acetate-ethylene emulsion, vinyl acetate-acrylate emulsion, and aqueous polyurethane dispersion.
[0015] A water-based antibacterial coating comprises the anionic stabilized water-based composition, pigments and fillers, dispersants, thickeners, defoamers, and film-forming aids described in any of the above technical solutions.
[0016] Beneficial effects: In this invention, monomer A contains a trialkoxy group and a long-chain quaternary ammonium group, exhibiting high functionality in the condensation reaction; monomer B contains two alkoxy groups, and after condensation, it mainly forms a D-type difunctional siloxane skeleton. In the first stage, monomer A is enriched, and only a portion of monomer B is added. The two first undergo co-hydrolysis and oligomerization reactions to reduce the content of free monomer A in the system, thus preventing a large amount of free monomer A from being directly exposed when an anionic emulsion is subsequently introduced. The amount of monomer B added is limited to 20-45% of the total amount to avoid premature formation of an excessively long hydrophobic skeleton or phase separation in the first stage.
[0017] Monomer C is a polyether-trialkoxysilane, which, after hydrolysis, can participate in subsequent condensation as a multifunctional crosslinking node. Its polyether chain reduces the effective exposure of cationic groups through hydration and steric hindrance. Monomer D contains only one hydrolyzable alkoxy group, which terminates or passivates part of the silanol end after condensation. Adding monomers C and D in the second stage allows them to effectively participate in the epitaxial growth of the oligomer in the first stage and the subsequent end-group regulation, thereby reducing the exposure density of cationic groups and avoiding disordered co-condensation with monomer A in the initial stage. The remaining monomer B provides connection and flexibility, preventing excessive crosslinking later. Monomer E contains a trialkoxy group and a glycidyl etheroxy group, and its silane end can participate in the Si-O-Si network. However, monomer E may partially hydrolyze or ring-open in an acidic aqueous phase. Therefore, this invention preferably adds it in the latter half of the second-stage premix preparation process, ensuring smooth hydrolysis and condensation of the silane component while reducing the possibility of premature ring-opening of the epoxy group. The addition of APG and EO / PO block polyethers can reduce the interfacial tension between the aqueous phase and the hydrophobic silane; the polyol, as a co-solvent and freeze-thaw stabilizer, is beneficial for easing the feeding process and low-temperature storage.
[0018] The use of stepwise vacuum during the preparation process can prevent instantaneous boiling and foam entrainment. After alcohol removal, water is added to make up the volume and pH is adjusted to prevent low-boiling alcohol residue from interfering with the volume making and causing deviations in solid content and residual alcohol detection data. Detailed Implementation
[0019] The technical solutions in the embodiments of this application will be clearly and completely described below with reference to the embodiments of this application. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.
[0020] All raw materials used in this invention are commercially available high-purity industrial-grade or analytical-grade. Monomer A is dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, 42wt% effective methanol solution; Monomer B is dimethyldiethoxysilane (purity ≥98%); Monomer C is methoxypolyethylene glycol-trimethoxysilane (average molecular weight 525.0 g / mol, effective content ≥99.0 wt%); Monomer D is trimethylmethoxysilane (purity ≥97.0 wt%); Monomer E is 3-glycidyloxypropyltrimethoxysilane (purity ≥98.0 wt%); Alkyl glycoside APG0810 (50 wt% aqueous solution); EO / PO block polyether: hydroxyl end group, nominal average molecular weight range 5900±500 g / mol, EO mass fraction 37%-43%, PO structural unit mass fraction is the balance, the sum of EO and PO structural unit mass fractions is 100%, hydroxyl value 17-22 mg. KOH / g, HLB value 12-14; propylene glycol (purity ≥99.5%, analytical grade).
[0021] Preparation of relevant solutions: 10wt% acetic acid solution: Add 800g of deionized water to the reactor, and slowly add 100.5g of 99.5% glacial acetic acid while stirring at room temperature. After the heat is completely released, add deionized water to make up to 1000g, mix well and set aside.
[0022] 5wt% sodium hydroxide solution: Add 800g of deionized water to the reactor, add 50g of sodium hydroxide in batches while stirring at room temperature, and continue stirring until the exothermic reaction ends and the solution cools to room temperature. Then, add deionized water to bring the total solution to 1000g, mix well, and set aside.
[0023] 1 mmol / L KCl solution: Weigh 0.0746 g of dried potassium chloride, dissolve it in deionized water and bring the volume to 1 L for zeta potential determination.
[0024] Example 1 A method for preparing an organosilicon-based antibacterial agent includes the following steps: S1. Add 150g deionized water, 80g propylene glycol, 20g APG0810 solution and 10g EO / PO block polyether to the reactor. Stir for 15min at 25±2℃ and 500r / min. Then slowly add 10wt% acetic acid solution to adjust the pH of the system to 3.80±0.05. Stir for at least 2min after each addition of acid and then take the reading. S2. Set the high-shear stirring speed to 4000 r / min. At 25-30℃, add 260 g of monomer A (42 wt% effective product, containing 0.220 mol of effective product A) to the bottom of the reactor within 30 min. After the addition is complete, continue high-shear stirring for 5 min. Maintain this high-shear state. Add the first-stage 26.7 g of monomer B (containing 0.180 mol of B, accounting for 34.6 wt% of the total B) and 40 g of deionized water together within 30 min. After the addition is complete, continue high-speed shear for 10 min, then adjust the stirring speed to 700 r / min. Introduce nitrogen to bring the system to a slightly positive pressure. Perform the hydrolysis reaction at 28±2℃ for 60 min, and take samples at 30 min and 60 min of hydrolysis respectively. Raise the temperature to 45±1℃ and hold at 600 r / min for 45 min. During this period, monitor closely to confirm that there is no stringing, lumps, or a continuous increase in torque. S3. In a closed reactor, 50.4g of monomer B (containing 0.340mol B), 73.5g of monomer C (containing 0.140mol C), and 9.5g of monomer E (containing 0.040mol E) from the second stage are mixed to obtain a premix (monomer B and monomer C are mixed first, and then monomer E is added); the temperature inside the reactor is maintained at 45-50℃, the high shear setting speed is set to 3000r / min, and the premix and 40g of deionized water are added together within 90min. 45min after the addition, 8.3g of monomer D (containing 0.080mol D) is added within 30-45min. During the addition process, the pH of the system is maintained at 3.80-4.20. S4. After feeding, adjust the speed to 600r / min, raise the temperature to 52±2℃ and keep it at the temperature for condensation for 150min. Take samples every 30min to test the viscosity at 25℃ and the Z-average colloidal particle size. S5. Maintain the temperature inside the reactor at 50±2℃, slowly start the vacuum pump to reduce the absolute pressure inside the reactor and stabilize it at 60kPa. Observe the foaming situation inside the reactor. When the foam gradually stabilizes within 5-10 minutes, further reduce the absolute pressure to 42kPa, and finally to 25kPa. Collect the fractions in stages and perform GC detection every 30 minutes. Stop when methanol ≤0.10wt% and ethanol ≤0.50wt%. Release the vacuum and introduce nitrogen gas. Cool to below 35℃, add water to 1000g, adjust the pH to 4.80-5.10, stir for 20 minutes, filter through a 100μm sieve to obtain the antibacterial product, which is sample numbered and named H1.
[0025] Example 2 This embodiment differs from Embodiment 1 in the following ways: In step S1, 160g of deionized water, 90g of propylene glycol, 25g of APG0810 solution and 12g of EO / PO block polyether were added to the reactor. After stirring for 15 minutes, the pH of the system was adjusted to 3.80±0.05 with 10wt% acetic acid solution.
[0026] In step S2, the high-shear setting speed is 4000 r / min. At 25-30℃, 213 g of monomer A (containing 0.180 mol of active ingredient A) is added to the bottom of the reactor within 30 min. Under this high-shear condition, 25 g of monomer B (containing 0.168 mol of B, accounting for 30 wt% of the total B) and 40 g of deionized water are added together within 30 min. After the addition is completed, the high-speed shear is continued for 10 min, and then the speed is adjusted to 700 r / min. The hydrolysis reaction is carried out at 28±2℃ under nitrogen protection for 60 min, and then kept at 45±1℃ for 45 min.
[0027] In step S3, in a closed reactor, 58g of monomer B (containing 0.392mol B), 84g of monomer C (containing 0.160mol C), and 4.73g of monomer E (containing 0.020mol E) from the second stage are mixed to obtain a premix (monomer B and monomer C are mixed first, and then monomer E is added); the temperature inside the reactor is maintained at 45-50℃, the high shear setting speed is turned on at 3000r / min, and the premix is added within 100min. 45min after the addition, 8.3g of monomer D (containing 0.080mol D) and 40g of deionized water are added within 30-45min. During the addition process, the pH of the system is maintained at 3.80-4.20. In step S4, the rotation speed is adjusted to 600 r / min, and the temperature is raised to 52±2℃ and held for condensation for 150 min.
[0028] In step S5, the vacuum was reduced in stages at 50±2℃, and the fractions were collected in stages for GC detection. The process was stopped when methanol ≤0.10wt% and ethanol ≤0.50wt%. The product was obtained by volume adjustment, pH adjustment and filtration, and the sample was numbered and named H2.
[0029] Example 3 This embodiment differs from Embodiment 1 in the following ways: In step S1, 170g of deionized water, 100g of propylene glycol, 30g of APG0810 solution and 15g of EO / PO block polyether were added to the reactor. After stirring for 15 minutes, the pH of the system was adjusted to 3.80±0.05 with 10wt% acetic acid solution. In step S2, the high-shear setting speed is 4000 r / min. At 25-30℃, 331 g of monomer A (containing 0.280 mol of active ingredient A) is added over 45 min. Under this high-shear condition, 26.7 g of monomer B (containing 0.180 mol of B, accounting for 37.5 wt% of the total B) from the first stage is added together with 45 g of deionized water over 30 min. After the addition is complete, high-speed shearing is continued for 10 min, and then the speed is adjusted to 700 r / min. Nitrogen gas is introduced and the hydrolysis reaction is carried out at 28±2℃ for 60 min. The temperature is then increased to 45±1℃ and held for 45 min. In step S3, in a closed reactor, 44.5g of monomer B, 63g of monomer C, and 11.8g of monomer E from the second stage are mixed to obtain a premix (monomer B and monomer C are mixed first, and then monomer E is added); the temperature inside the reactor is maintained at 45-50℃, and the premix and 45g of deionized water are added together over 120min at a rotation speed of 3000r / min. 45min after the addition, 7.3g of monomer D is added over 30-45min, and the pH of the system is maintained at 3.80-4.20. In step S4, after the material is added, adjust the rotation speed to 600 r / min, raise the temperature to 52±2℃ and hold for polycondensation for 180 min; In step S5, the vacuum was reduced in stages at 50±2℃, and the fractions were collected in stages for GC detection. The process was stopped when methanol ≤0.10wt% and ethanol ≤0.50wt%. The product was obtained by volume adjustment, pH adjustment and filtration, and the sample was named H3.
[0030] Comparative Example 1 Compared with Example 1, this comparative example only changes the order of feeding; all other aspects are the same as in Example 1, as follows: 260g of monomer A, 77g of monomer B, 73.5g of monomer C, 8.3g of monomer D, and 9.5g of monomer E were premixed in a closed system and added in one batch over 90 minutes at 25-30℃ and a high shear rate of 4000r / min, along with 80g of water. The mixture was then hydrolyzed for 60 minutes and kept at 45℃ for 45 minutes (the total thermal history of the system was made similar to that in Example 1 by additional heat treatment). Subsequently, the mixture was polycondensed at 52±2℃ for 150 minutes. After alcohol removal, volume adjustment, and filtration, the product was obtained, and the sample number was M1.
[0031] Comparative Example 2 Compared with Example 1, the monomers and feed amounts in this comparative example are the same as in Example 1, but the order of monomer addition is changed. The rest is the same as in Example 1, as follows: In the first stage, 26.7g of monomer B, 73.5g of monomer C, and 8.3g of monomer D were added together with 40g of water over 60 minutes. Hydrolysis was carried out for 60 minutes and then kept at 45±1℃ for 45 minutes. In the second stage, 260g of monomer A, 50.4g of monomer B, and 9.5g of monomer E were added together with 40g of water over 90 minutes. Polycondensation was then carried out at 52±2℃ for 150 minutes. After alcohol removal, volume adjustment, and filtration, the product was obtained, and the sample number was M2.
[0032] Comparative Example 3 Compared with Example 1, in this comparative example, monomer C was not added during the preparation process. Instead, monomer C in Example 1 was supplemented with an equimolar amount of monomer B. All other steps were the same as in Example 1. The product sample was numbered M3.
[0033] Comparative Example 4 Compared with Example 1, in this comparative example, monomer D was not added during the preparation process. Instead, monomer D in Example 1 was supplemented with an equimolar amount of monomer B. All other steps were the same as in Example 1. The product sample was numbered M4.
[0034] Related tests: I. Physical properties and stability characterization: Filtration recovery rate: After the sample is replenished with water and the pH is adjusted, the total mass of the material before filtration, m1, is weighed; the sample is filtered through a 100μm nylon sieve, and all the filtrate is collected and weighed, recorded as m2. The calculation formula is: Filtration recovery rate / % = m2 / m1 × 100%.
[0035] Non-volatile matter content (solid content): Weigh approximately 1.0 g of sample, dry at 105±2℃ to constant weight, and calculate the percentage of the mass of the residue relative to the mass of the initial sample.
[0036] Viscosity: The viscosity of the water dispersion was measured at 25.0±0.1℃ using an NDJ-1 type rotational viscometer. The test method was as follows: the test rotation speed was 60r / min, and the rotor was selected according to the following rules so that the instrument pointer reading was within 20%-80% of the full scale: (1) When the expected viscosity was 10-100mPa·s, rotor No. 1 was used; (2) When the expected viscosity was 50-500mPa·s, rotor No. 2 was used; (3) When the expected viscosity was 200-2000mPa·s, rotor No. 3 was used; (4) When the expected viscosity was 1000-10000mPa·s, rotor No. 4 was used. After starting the instrument, the value was read at 60s. If the reading change was less than 5% within 60-120s, the reading at 120s was taken as the test result. If the reading continued to change by more than 5%, or if glue blocks appeared around the rotor, or if the sample could not form a continuous and uniform flow state, it was recorded as that a stable apparent viscosity could not be obtained.
[0037] DLS particle size and polydispersity index (PDI): The aqueous dispersion sample was diluted with deionized water to a non-volatile content of 0.10 wt%, ultrasonically dispersed, and then equilibrated at 25°C for 5 min using a Malvern nanoparticle size analyzer. The Z-mean particle size and PDI were measured and the data were recorded.
[0038] Zeta potential: The sample was dispersed in a prepared 1 mmol / L KCl solution at a non-volatile content of 0.10 wt%, and the pH was adjusted to 5.0 ± 0.1. The zeta potential value was tested and recorded at 25 °C.
[0039] GC detection of residual alcohol: Residual methanol and ethanol were determined by headspace sampling-gas chromatography-flame ionization detection and quantified using the internal standard method. The internal standard was tert-butanol. A 2.00 g / L tert-butanol internal standard aqueous solution was prepared. 1.0000 ± 0.0010 g of the sample to be tested was accurately weighed and placed in a 20 mL headspace sampling bottle. 5.00 mL of saturated sodium chloride aqueous solution and 1.00 mL of tert-butanol internal standard aqueous solution were added. The bottle was immediately sealed and mixed thoroughly. The headspace injection conditions were as follows: headspace vial equilibration temperature 60℃, equilibration time 30 min, transfer tube temperature 80℃, and quantitative loop volume 1.0 mL. The gas chromatography conditions were as follows: polyethylene glycol stationary phase capillary column, 30 m × 0.32 mm × 0.50 μm; carrier gas nitrogen, constant flow mode, flow rate 1.5 mL / min; injection port temperature 150℃; split ratio 10:1; initial column temperature 40℃ for 5 min, then increased to 120℃ at 10℃ / min and held for 2 min; FID detector temperature 250℃. The peak areas of methanol and ethanol were corrected using the peak area of tert-butanol internal standard, respectively. The correlation coefficient R of the calibration curve was... 2 It should be no less than 0.995.
[0040] High-temperature storage stability: Place the aqueous dispersion sample in a sealed wide-mouth bottle and let it stand in a constant temperature oven at 50.0±1.0℃ for 30 days. After removing it and restoring it to room temperature, observe whether it separates into layers, precipitates, or gels, and retest the viscosity.
[0041] The test results are shown in Table 1.
[0042] Table 1. Test results of physical properties and stability
[0043] The test results above show that the filtration recovery rates of the products prepared in Examples 1 to 3 are significantly higher than those in Comparative Examples 1 to 4. The product prepared in Example 1 exhibits a more balanced overall performance in terms of storage stability, emulsion compatibility, and antibacterial durability. This indicates that the first stage, which hydrolyzes quaternary ammonium silane A with some skeletal silane B to form an oligomeric structure, followed by the introduction of polyether silane C, end-capping silane D, remaining monomer B, and monomer E in the second stage, can effectively inhibit the local excessive condensation polymerization of trifunctional quaternary ammonium silanes.
[0044] II. Anionic Emulsion Cup Test An anionic stable commercial styrene-acrylic emulsion (48 wt% solids, pH 8.0, anionic emulsion system) was selected as the master model for mixture evaluation. The experimental procedures are as follows: 1. Take the sample to be tested, pre-dilute it with deionized water at a mass ratio of 1:5, stir gently for 5 minutes and let it stand for 10 minutes to prepare the pre-diluted solution; 2. Add 200g of styrene-acrylic emulsion to a beaker and stir at 400r / min in a water bath at 25±1℃. Within 5min, slowly and evenly add the pre-diluted solution to the emulsion so that the modified polysiloxane aqueous dispersion (on a dry basis) accounts for 0.50wt% of the total mass of the emulsion. After the addition is complete, continue stirring at 400r / min for 15min. 3. Immediately after the addition of materials, and after sealing and standing at 25°C for 24 hours and 7 days, record the appearance changes of the mixed emulsion, and record whether there are coarse particles, local lumps, severe bubbles and demulsification sediment. 4. The change rate (%) of system viscosity and latex particle size after 24 hours of addition was detected using an NDJ-1 viscometer and a DLS particle size analyzer. 5. Pass 100g of the mixture after 24 hours of addition through a 100μm nylon sieve that has been pre-dried to constant weight at 60℃. Rinse the sieve with sufficient deionized water and dry it at 60℃ to constant weight. Calculate the percentage of the mass of the dried filter residue on the sieve surface relative to the total mass of the test material.
[0045] The test results are shown in Table 2.
[0046] Table 2 Emulsion compatibility results
[0047] The test results above show that the product prepared in Example 2, when mixed with styrene-acrylic emulsion, forms a homogeneous system. After 24 hours, the viscosity increases by only 4.7%, the latex particle size increases by 6.8%, and the 100μm filter residue is only 0.014%. After 7 days, the system remains homogeneous without stratification. This result is consistent with the data measured in Table 1, indicating that a higher proportion of polyether silane C can form more sufficient hydration on the outside of the particles, reducing the instantaneous charge complexation between quaternary ammonium cations and anionic emulsifiers and anionic latex particles, and improving the storage stability of the system.
[0048] III. Antibacterial Properties and Durability Tests Preparation of standard white interior wall latex paint containing a product antibacterial agent (addition amount of 0.50wt%): Taking a 0.5wt% product antibacterial agent concentrate as an example, take 495g of base white latex paint, stir at 300r / min at 25℃, mix 2.5g of antibacterial agent concentrate with 2.5g of deionized water to dilute, and slowly add it dropwise to the latex paint within 5min, continue to disperse at a medium speed of 500r / min for 15min, and adjust the pH to 8.0±0.2 with ammonia water to prepare antibacterial latex paint. Prepare coatings of the same dry film thickness on the same batch of standard substrates using the same applicator, and cure at 23±2℃ and 50±5%RH for 7d. Test according to the relevant provisions of GB / T 21866-2025, the test strains are Staphylococcus aureus and Escherichia coli, and record the initial antibacterial rate; after testing the initial antibacterial performance, perform 30 and 50 standard scrubs respectively, and then retest the antibacterial performance. The test results are shown in Table 3.
[0049] Table 3 Antibacterial properties and durability tests
[0050] The test results above show that the example maintained a high antibacterial rate after 50 washes, while the comparative example showed a significant decrease.
[0051] It should be noted that, in this document, the terms “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0052] Although embodiments of this application have been described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of this application, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an organosilicon-based antibacterial agent, characterized in that, The antibacterial agent is prepared from raw materials including monomers A, B, C, D and E, wherein: monomer A is a long-chain alkyl quaternary ammonium trialkoxysilane, monomer B is a dialkyl diekoxysilane, monomer C is a polyether trialkoxysilane, monomer D is a trialkyl monoalkoxysilane, and monomer E is an epoxy-functionalized trialkoxysilane. The preparation method includes the following steps: S1. Solution preparation and acidification: Mix deionized water, nonionic surfactant and polyol, and adjust the pH of the system to 3.7-4.2 with organic acid; S2, First-stage hydrolysis and oligomerization: Add 70-100% of the total amount of monomer A and 20-45% of the total amount of monomer B at 25-32℃. The amount of monomer C added in the first stage shall not exceed 20% of the total amount of monomer C, and the amount of monomer D added in the first stage shall not exceed 40% of the total amount of monomer D. After the addition is completed, hydrolyze for 60-120 minutes and keep warm at 42-47℃ for 30-60 minutes to obtain the first-stage oligomer. S3, Second stage co-condensation: Add the remaining amount of monomer C, monomer D, monomer A, monomer B and monomer E within 90-150 min at 45-50℃. S4. Thermal polycondensation: Polycondensate at 50-56℃ for 1.5-3.5h to obtain a coarse dispersion of polycondensate; S5. Staged de-alcoholization and post-treatment: Vacuum is established stepwise at 48-53℃ to remove hydrolysis by-product alcohols and low-boiling alcohols carried by the raw materials. After cooling, the pH is adjusted and water is added to make up the volume to obtain the product antibacterial agent.
2. The method for preparing an organosilicon-based antibacterial agent according to claim 1, characterized in that, The general structural formula of monomer A is: [R 1 N + [(CH3)2(CH2)3Si(OR2)3]X - , where R 1 R is a C12-C18 straight-chain or branched alkyl group. 2 Methyl or ethyl, X - The monomers are chloride or bromide ions; monomer B is dimethyldimethoxysilane or dimethyldiethoxysilane; monomer C is polyethertrimethoxysilane or polyethertriethoxysilane; monomer D is trimethylmethoxysilane or trimethylethoxysilane; monomer E is 3-glycidoxypropyltrimethoxysilane or 3-glycidoxypropyltriethoxysilane.
3. The method for preparing an organosilicon-based antibacterial agent according to claim 1, characterized in that, In the first stage, 90-100% of the total amount of monomer A and 25-40% of the total amount of monomer B are added, and monomers C and D are not added in the first stage; in the second stage, all of monomer C, all of monomer D, the balance of monomer A, the balance of monomer B, and monomer E are added.
4. The method for preparing an organosilicon-based antibacterial agent according to claim 1, characterized in that, The nonionic surfactant is an EO / PO block polyether and / or an alkyl glycoside; the polyol is propylene glycol and / or dipropylene glycol.
5. The method for preparing an organosilicon-based antibacterial agent according to claim 1, characterized in that, The organic acid is one or more of acetic acid, lactic acid, and citric acid.
6. The method for preparing an organosilicon-based antibacterial agent according to claim 1, characterized in that, In step S5, the vacuum is established step by step by reducing the absolute pressure from 50-70 kPa to 35-50 kPa, and then to 20-35 kPa. The gas chromatography detection is used as the endpoint to control the residual methanol content in the product to be no higher than 0.10 wt% and the residual ethanol content to be no higher than 0.50 wt%.
7. An organosilicon-based antibacterial agent, characterized in that, The antibacterial agent is prepared by the method described in any one of claims 1-6; the non-volatile content of the antibacterial agent is 20-30 wt%, and the pH is 4.7-5.
2.
8. An anion-stabilized aqueous composition, characterized in that, The composition comprises a polymer emulsion and the antimicrobial agent of claim 7, wherein the antimicrobial agent comprises 0.05-1.5 wt% of the total mass of the aqueous composition.
9. The anion-stabilized aqueous composition according to claim 8, characterized in that, The polymer emulsion is one or more of the following: styrene-acrylate emulsion, pure acrylate emulsion, vinyl acetate-ethylene emulsion, vinyl acetate-acrylate emulsion, and aqueous polyurethane dispersion.
10. A water-based antibacterial coating, characterized in that, It comprises the anionic stabilized aqueous composition according to any one of claims 8-9, pigments, fillers, dispersants, thickeners, defoamers, and film-forming aids.